Analisis Yuridis Terhadap Pelaku Tindak Pidana Penganiayaan Anak (Studi Putusan: Nomor 2561/PID.SUS/2022/PN MDN) - Sihombing, Bastian; Marlina, Marlina; Trisna, Wessy (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
Child abuse not only causes material losses but also profound psychological impacts, such as emotional and psychological trauma. One case of child abuse is recorded in Decision Number 2561/Pid.Sus/2022/PN Mdn. In this case, the defendant M. Syafri, also known as Muhammad Saprik, committed violence against a child, Abdan Yolanda Lubis, causing a torn wound on the child’s left ring finger. As a result, the defendant was sentenced to 2 years in prison. Based on Law Number 23 of 2022 on Child Protection, Article 80, paragraph (1) stipulates that perpetrators of child abuse, such as assault, can be sentenced to a maximum of 3 years and 6 months in prison, without the possibility of detention. The method used in this study is normative legal research, descriptive-analytical in nature, employing both a statutory approach and a case study approach. This research uses secondary data consisting of primary, secondary, and tertiary legal materials. The analysis results indicate that the legal provisions regarding the detention of perpetrators of child abuse are regulated in Article 76C of Law Number 35 of 2014. The law prohibits anyone from committing violence against children, either directly or through an order. Legal protection for children who are victims of abuse is carried out preventively through law enforcement and repressively through socialization to children and related institutions. The analysis of the verdict indicates that the punishment imposed on the defendant is considered too lenient and does not match the suffering experienced by the victim. The prosecutor's demands and the ruling are not maximal, while the law stipulates a prison sentence of 3 years and 6 months and/or a fine of up to IDR 72,000,000.